"Much ado to know myself...": Insight in the talking cures - Jopling, David A. (Annals of the New York Academy of Sciences, 2011)
Psychoanalysis, psychodynamic psychotherapy, and the other talking cures claim to help clients acquire insight into their selves. With insight, the unruly forces that govern lives and that make people strangers to themselves finally come to be understood and rendered subject to conscious control. These insights, it is claimed, are true, and fit the facts like a key fits a lock; they are not merely coherent fictions or confabulated cause‐and‐effect stories designed to please clients. But is this credible? The argument developed here is that some of the therapeutic changes in the talking cures are functions of placebos that rally the mind's native healing powers in much the same way that placebo pills rally the body's native healing powers and that some of these placebos are insight placebos. The talking cures rightfully claim that it is only talking with others that unlocks the soul and opens it up to ways of self‐knowing and to caring for self that would otherwise be unavailable, but they fail to acknowledge the presence of placebo effects, and they operate with restrictive models of dialogue that may unintentionally encourage placebo effects and cognitive suggestibility.